2019
DOI: 10.1186/s40001-019-0375-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of epithelioid hemangioendothelioma: a single-center retrospective study

Abstract: Background Epithelioid hemangioendothelioma (EHE) is a rare malignant vascular neoplasm with increasing incidence. However, its clinical characteristics remain unclear due to its low incidence. This study aimed to investigate the features of EHE. Methods Patients with EHE treated at our institution between January 2000 and June 2018 were enrolled. Data including demographic characteristics, treatment patterns, pathological results, and prognosis were collected, and a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
0
23
2
5
Order By: Relevance
“…Although EHE is often reported to be heterogeneous [7,24], the present study is the first to demonstrate this diversity by identification of three symptom clusters. Previous data are limited to prevalence of symptoms rather than examining the symptom burden of individual patients [2,3,25]. In the present study, 87% of patients reported one or more symptoms, compared to 45-72% symptomatic EHE patients in previous studies [2,3,25].…”
Section: Discussioncontrasting
confidence: 51%
“…Although EHE is often reported to be heterogeneous [7,24], the present study is the first to demonstrate this diversity by identification of three symptom clusters. Previous data are limited to prevalence of symptoms rather than examining the symptom burden of individual patients [2,3,25]. In the present study, 87% of patients reported one or more symptoms, compared to 45-72% symptomatic EHE patients in previous studies [2,3,25].…”
Section: Discussioncontrasting
confidence: 51%
“…Surgery is the treatment of choice in local disease. There is a risk of metastatic disease (synchronic or metachronic) and a significant mortality rate (up to 45%) [58][59][60].…”
Section: Epithelioid Hemangioendothelioma (Ehe)mentioning
confidence: 99%
“…Patients with unresectable primary tumor or distant metastases were diagnosed via biopsy and did not undergo resection. Such patients showed high mortality [ 19 ].…”
Section: Discussionmentioning
confidence: 99%